Effect of Vascular Endothelial Growth Factor siRNA-loaded Nanoparticles with Doxorubicin in Inhibiting the Growth of Breast Cancer in Xenograft Mouse Model - Xuanhe Li; Siyu Sun; Xicheng Yue; Song Zhang; Liyu Qian; Jie Tang; Fangqian Jiang; Jianfei Lu; Yifan Cao; Shengwen Meng; Tingjing Yao (Journal of Animal and Plant Sciences, 2025)
As an antineoplastic antibiotic, doxorubicin (DOX) effectively inhibits RNA and DNA synthesis. However, its application is limited by side effects and drug resistance. This study established a xenograft mouse model of breast cancer (BC) to investigate the therapeutic efficacy of a gene/drug nano-delivery system combining vascular endothelial growth factor (VEGF) silencing with DOX for treating BC. Poly (lactic acid) (PLA) was utilized as the carrier material to prepare nanoparticles (NPs) loaded with VEGF interference RNA (siRNA) and the chemotherapeutic drug DOX (PLA/DOX-NPs and PLA/DOX-siVEGF-NPs). The characterization and drug release of NPs were analyzed. NPs’ cytotoxicity was determined by CCK-8 assay with HUVEC and MCF-7 cells. The BC xenograft (BCX) model was established by injecting MCF-7 cells into the mammary fat pads of nude mice. The differences in tumor weight and tumor inhibition rate were analyzed after treatment with DOX alone, PLA/DOX-NPs, and PLA/DOX-siVEGF-NPs. Immunohistochemical staining was employed to examine Ki-67 positive expression rate in the BCXs. Western blot was used to detect Ki-67 and VEGF protein expression levels in transplanted tumor tissues. Additionally, a suspension of BCX cells was injected subcutaneously into healthy nude mice to assess tumor growth after secondary engraftment. Both PLA/DOX-NPs and PLA/DOX-siVEGF-NPs demonstrated sustained release of DOX in buffer media at varying pH values, with no visible difference in inhibiting human umbilical vein endothelial cells (HUVECs) proliferation. After establishment of the BCX mouse model, compared to DOX group, the PLA/DOX-NPs group and PLA/DOX-siVEGF-NPs group exhibited a significant reduction in relative tumor volume and Ki-67 index, along with an increased tumor inhibition rate. Furthermore, after secondary tumor formation, both tumor volume and size were markedly reduced (P<0.05). There were statistically significant differences in various parameters between the PLA/DOX-NPs group and the PLA/DOX-siVEGF-NPs group (P<0.05). The prepared PLA/DOX-siVEGF-NPs demonstrated low toxicity to normal cells and strongly inhibited the proliferation of MCF-7 BC cells in vitro. Moreover, PLA/DOX-siVEGF-NPs effectively inhibited the growth of BCXs in nude mice and suppressed Ki-67 positive expression. This treatment also reduced the malignant differentiation of the tumors and inhibited tumor recurrence.
Keywords: xenograft mouse model; doxorubicin; nanoparticles; breast cancer; vascular endothelial growth factor